Perdue Farms: A Vertically Integrated Supply Chain - Munson, Chuck (Charles Lee); Li, Ling (Pearson, 2013)
This new case study examines the remarkable vertically integrated supply chain built by Perdue Farms, which supplies 2.7 billion pounds of poultry annually to customers in more than 40 countries. It reviews processes across the entire supply chain, from breeding eggs and hatching chicks through manufacturing processing, packaging, warehousing, and distribution and also addresses Perdue's current strategies, competitors, and challenges. Focusing on realistic issues and challenges throughout, this case study offers exceptional value to both students and practitioners. Author: Ling Li, Old Dominion University.